Impact of sled loads on velocity during acceleration phase from starting blocks - Elmontassar, W.; Mkaouer, B.; Racil, G.; Rommene, I.; Coquart, J.; Ben Moussa, A. Z.; Ben Salah, F. Z. (South African Journal for Research in Sport, Physical Education and Recreation, 2018)
Sprinters use the weighted sled to improve acceleration ability starting with the standing position, but little information is available. The purpose of this study was to examine the effect of sled loads on velocity achieved during a short distance sprint from the starting block and to develop a regression equation to determine the sled load in relation to the body mass (BM). Twenty-two male sprint athletes (age: 21.1±2.2 years; height: 178±6.0cm; body mass: 73.5±9.5kg; competitive experience=6.4±1.0yrs; personal best performance in 100m=11.05±0.27secs) performed five sprints over a distance of 15m from starting blocks on a synthetic surface and with track shoes (loaded conditions: 7%, 10%, 15% and 20% of BM). Sprint time for 15m under the four loaded conditions was significantly lower than the unloaded condition (p 0.05). The results led to determining a regression equation to calculate the load that can be used with sled-towing when sprinting from starting blocks (Equation: %BM= -1.48 (% velocity)+148.85). This equation may be an appropriate tool for coaches to optimise training sessions for male sprinters.